PENGARUH LATIHAN KEKUATAN OTOT TUNGKAI TERHADAP JAUHNYA TENDANGAN PADA PEMAIN SEPAK BOLA PSDKU ARU - Maita, Gidion S; Syaranamual, Jusak; Somarwain, Falerius. (Porgram Studi Diluar Kampus Utama (PSDKU) Universitas Pattimura Program Studi Pendidikan Jasmani, 2023)
Football game is one of the sports that is of interest to Patimura University students of the Outside Main Campus Study Program (PSDKU ARU), who often appear with PSDKU ARU soccer players at soccer championships held in the city of Dobo. As well as in the student league